No Trace Anywhere of Life, Perhaps: Autology and Hauntology in Imagination Dead Imagine. Issue 2 (September 2022) - Vozel, François-Nicolas
Abstract : This essay interprets Imagination Dead Imagine as the product of Beckett's own autology, in Arnold Geulincx's sense of the term. The Cartesian occasionalist advanced that self-inspection culminates with the revelation of human beings' fundamental ignorance and impotence. I suggest that the short text borrows Geulingian themes and imagery to offer a dazzling vision – from the point of view of eternity – of the radical atomization and opacity of the human condition. Furthermore, I explore how Beckett generates a specifically Geulingian commentary on a debate that obsessed him throughout his life: the problem of the subject-object relation and the self-to-self relation in artistic representation. Finally, I propose to read the paradoxical imperative 'imagination dead imagine' as a Geulingian axiom in its own right, that is, as an inescapable obligation whose fulfilment is quasi-impossible.